The association between Staphylococcus aureus and subsequent bronchiectasis in children with cystic fibrosis - Caudri, D.; Turkovic, L.; Ng, J.; de Klerk, N.; Rosenow, T.; Hall, Graham; Ranganathan, S.; Sly, P.; Stick, S. (Elsevier, 2018)
© 2017 European Cystic Fibrosis Society. Background: Staphylococcus aureus (S. aureus) may be related to more rapid progression of cystic fibrosis (CF) lung disease. Methods: In the AREST CF cohort study, children diagnosed with CF undergo annual bronchoscopies with bronchoalveolar lavage and ultra-low-dose, chest computed tomography (CT) up to 6-years-old. Spirometry was assessed 3-monthly from the age of 4. years. Associations between de novo S. aureus acquisition before school age and CT and lung function at ages 5-7. years were investigated. Models were adjusted for multiple markers of disease severity at baseline. Results: De novo S. aureus acquisition at 3-years-old (n/N=12/122) was associated with increased bronchiectasis score at age 5-6years. This association decreased but remained significant after adjustment for confounders. S. aureus at 3 was associated with significantly reduced FEF 25-75 at age 5-7years, but not with FEV 1 -%-predicted. Conclusion: De novo S. aureus acquisition at age 3 is associated with later bronchiectasis and FEF 25-75 in children with CF.